If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4y = -2 Solving 6 + -4y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -4y = -2 + -6 Combine like terms: 6 + -6 = 0 0 + -4y = -2 + -6 -4y = -2 + -6 Combine like terms: -2 + -6 = -8 -4y = -8 Divide each side by '-4'. y = 2 Simplifying y = 2
| 55=7k | | sin(x)=-0.2523 | | 6h+6=7h | | X+2.5=y | | 2k-4=28 | | 17=5+2x+2 | | (2w+5)(4w-6x-7)= | | (7-4i)(5-2i)=0 | | h(x)=x^4+7x^2+7 | | 10-17x+7x^2=0 | | -6x-6y-4x+15y= | | 5t^2+2t-3=0 | | Ln(0.01+1)= | | 13-(-9x)+3x-(-11)= | | 9-2x=9-7x | | 7m^2-28m-224=0 | | 2b-4-9b-9= | | x-0.5x-0.75x-0.5x=200 | | 8/27+1/9+4/9= | | 5x^4*2x^3= | | 0=-4x^2+24x+12 | | 9(n+2)+8n+7= | | .25+.6(50-m)=0 | | 15a^2-3ab-18b^2=0 | | 3x^2+12=66 | | 4v-8=4v-12 | | 1+6y-16y= | | 3x-19x= | | -3y+2=10y+30 | | 2z+.6=3z+.2 | | f(x)=-x^4+x^2 | | 26-2x=10+6x |